Climates Past, Present, and Yet-to-Come Shape Climate Change Vulnerabilities. (October 2017) - Nadeau, Christopher P.; Urban, Mark C.; Bridle, Jon R.
Abstract : Climate change is altering life at multiple scales, from genes to ecosystems. Predicting the vulnerability of populations to climate change is crucial to mitigate negative impacts. We suggest that regional patterns of spatial and temporal climatic variation scaled to the traits of an organism can predict where and why populations are most vulnerable to climate change. Specifically, historical climatic variation affects the sensitivity and response capacity of populations to climate change by shaping traits and the genetic variation in those traits. Present and future climatic variation can affect both climate change exposure and population responses. We provide seven predictions for how climatic variation might affect the vulnerability of populations to climate change and suggest key directions for future research. Trends: Predicting the vulnerability of populations to climate change is crucial. Spatial and temporal climatic variation strongly influence vulnerability. Historical climatic variation can shape traits that affect vulnerability. Present and future climatic variation affect exposure and population responses. Maps of climatic variability can predict where populations are most vulnerable.